INTERNET AND SOCIAL IN YOUTH SOCIALIZATION EFFECT OF NETWORKS - Jalilova Muhayyo (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
The information provided discusses the influence of the internet on today's youth and offers recommendations to mitigate potential risks. It highlights the dangers posed by opening emails from unknown senders, emphasizing the possibility of harmful viruses or programs. Additionally, it stresses the importance of safeguarding personal passwords and refraining from sharing them. The text also advises against responding to unnecessary messages or offers and suggests reporting such incidents to parents or guardians. Finally, it emphasizes the significance of avoiding websites intended for adults only. Overall, the annotation underscores the importance of recognizing both the positive and negative impacts of internet usage and urges individuals to use it responsibly.